GILT: Shaping the MHC Class II-Restricted Peptidome and CD4+ T Cell-Mediated Immunity - Hastings, Karen T. (Frontiers in Immunology, 2013)
The MHC class II-restricted antigen processing pathway generates peptide:MHC complexes in the endocytic pathway for the activation of CD4+ T cells. Gamma-interferon-inducible lysosomal thiol reductase (GILT) reduces protein disulfide bonds in the endocytic compartment, thereby exposing buried epitopes for MHC class II binding and presentation. T cell hybridoma responses and elution of MHC class II bound peptides have identified GILT-dependent epitopes, GILT-independent epitopes, and epitopes that are more efficiently presented in the absence of GILT termed GILT-prevented epitopes. GILT-mediated alteration in the MHC class II-restricted peptidome modulates T cell development in the thymus and peripheral tolerance and influences the pathogenesis of autoimmunity. Recent studies suggest an emerging role for GILT in the response to pathogens and cancer survival.